Linking Dietary Patterns to Autism Severity and Developmental Outcomes: A Correlational Study Using Food Frequency Questionnaires; The Childhood Autism Rating Scale, Second Edition; And Developmental Profile 3 - Dimitar Marinov; Sevdzhihan Eyubova; Albena Toneva; Rositsa Chamova; Rozalina Braykova; Stanislava Hadzhieva; Ruzha Pancheva (Biomedicines)
Background/Objectives: Autism Spectrum Disorder (ASD) is characterized by social communication challenges and repetitive behaviors. Children with ASD often exhibit selective eating habits that may result in nutritional deficiencies and exacerbate developmental issues. While food frequency questionnaires (FFQs) are effective for dietary assessment, the links between food preferences, ASD severity, and developmental outcomes remain underexplored, particularly in Bulgaria. This study examines these relationships using validated tools. Methods: The present report constitutes a pilot, hypothesis-generating substudy of the broader NutriLect project. This substudy involved 49 children aged 2–12 years diagnosed with ASD. Dietary patterns were evaluated with a modified FFQ, while ASD severity and developmental profiles were assessed using the Childhood Autism Rating Scale, Second Edition (CARS-2) and the Developmental Profile 3 (DP-3). Results: Among 49 ASD children (mean age = 6.89 ± 2.15 years; 86% boys), 73.4% consumed grains/potatoes daily. Only 34.7% met combined fruit and vegetable recommendations. Only 36.7% met the recommendation for daily milk or other dairy product consumption. Fish was consumed at least twice weekly by only 22,4%. Furthermore, children with more severe autism were approximately 9.4 times more likely to consume grains daily (χ2 = 14.319, p = 0.006). Logistic regression analyses indicated that higher cognitive scores were strongly associated with lower grain (OR ≈ 0.044) and other dairy products consumption (OR ≈ 0.337), yet with greater fish intake (OR ≈ 3.317). In contrast, better communication skills corresponded to increased milk consumption (OR ≈ 5.76), and higher physical development scores predicted more frequent egg consumption (OR ≈ 4.40). Conclusions: The pronounced preference for grain and meat products, which are frequently ultra-processed, and avoidance of nutrient-dense foods in children with severe ASD symptoms underscore the need for tailored dietary interventions. These interventions must address sensory sensitivities, nutritional inadequacies, and the risks that selective nutrition can have on the nutritional status and development of the children.